Guardians of Horsa. [1], Legend of the yearling - Black, Roan (Black, Roan. Guardians of Horsa, 2023)
The herds of magical horses in Horsa have a fragile alliance, but when a prophecy stating that a yearling with a new kind of magic has been born, the four herds each elect a group of horses to find the yearling and bring balance to Horsa.